A novel module of MaMADS31-MaBZR2 confers negative regulation of banana fruit ripening - Chaojie Wu; Wei Wei; Danling Cai; Zengxiang Lin; Yingying Yang; Jia Si; Wei Shan; Jianye Chen; Wangjin Lu; Jianfei Kuang (Horticultural Plant Journal)
Fruit ripening, which is modulated by the up- and downregulation of numerous genes, is a sophisticated physiological event determining consumer acceptability. While many positive regulators have been known to regulate fruit ripening, relatively less information is associated with the negative regulators in the process. Here, a negative regulator, MaMADS31, was characterized according to the banana fruit ripening transcriptome, which displayed nuclear localization and inhibitory transactivation activity. MaMADS31 suppresses the transcription of the cell wall modification gene MaPL15 and the ethylene biosynthesis-related gene MaACO13 by directly recognizing the CArG-box element in their promoters. Transient expression of MaMADS31 in banana fruit brought about downregulation of MaPL15 and MaACO13, thereby delaying fruit ripening. Importantly, MaMADS31 interacts with MaBZR2 to synergistically strengthen the transcriptional inhibition of MaPL15 and MaACO13. Overall, MaMADS31-MaBZR2 plays a negative role in fruit ripening by downregulating the MaPL15 and MaACO13 transcription, which provides new insights for innovating approaches for prolonging the postharvest life of horticultural plants.